On winds - Theophrastus. (Philosophia Antiqua, 2017)
In Theophrastus of Eresus: On Winds , Robert Mayhew provides a critical edition of the Greek text with English translation and commentary on the sole Peripatetic treatise devoted specifically to winds, by Aristotle's successor in the Lyceum. This is the first edition of this text to appear in over forty years, and the first ever to make use not only of the twelve medieval manuscripts but also of the Oxyrhynchus papyrus fragment of this work (first published in 1986). The lengthy commentary attempts to explain this difficult (and often corrupt) text and its relationship to Aristotle's meteorological theory and scientific methodology.